Video Games for Well-Being: A Systematic Review on the Application of Computer Games for Cognitive and Emotional Training in the Adult Population - Pallavicini, Federica; Ferrari, Ambra; Mantovani, Fabrizia (Frontiers in Psychology, 2018)
Background. Although several excellent reviews and meta-analyses have investigated the effect of video game trainings as tools to enhance well-being, most of them specifically focused on the effects of digital games on brain plasticity or cognitive decline in children and seniors. On the contrary, only one meta-analysis results to be focused on the adult population, and it is restricted to examining the effects of training with a particular genre of games (action video games) on cognitive skills of healthy adults. Objectives. This systematic review was aimed to identify research evidences about the impact on cognitive (i.e., processing and reaction times, memory, task-switching/multitasking, and mental spatial rotation) and emotional skills of video games training in the healthy adult population. Methods. A multi-component analysis of variables related to the study, the video games, and the outcomes of the training was made on the basis of important previous works. Databases used in the search were PsycINFO, Web of Science (Web of Knowledge), PubMed, and Scopus. The search string was: [(“Video Games” OR "Computer Games" OR "Interactive Gaming")] AND [(“Cognition”) OR ("Cognitive") OR ("Emotion") OR ("Emotion Regulation”)] AND ["Training"]. Results. 35 studies met the inclusion criteria and were further classified into the different analysis’ variables. The majority of the retrieved studies used commercial video games, and action games in particular, which resulted to be the most commonly used, closely followed by puzzle games. Effect sizes for training with video games on cognitive skills in general ranged from 0.06 to 3.43: from 0.141 to 3.43 for processing and reaction times, 0.06 to 1.82 for memory, 0.54 to 1.91 for task-switching/multitasking, and 0.3 to 3.2 for mental spatial rotation; regarding video games for the training of emotional skills, effect sizes ranged from 0.201 to 3.01. Conclusion. Overall, findings give evidences of benefits of video games training on cognitive and emotional skills in relation to the healthy adult population, especially on young adults. Efficacy has been demonstrated not only for non-commercial video games or commercial brain-training programs, but for commercial video games as well.